The modular multilevel converter for high step-up ratio DC-DC conversion - Zhang,X; Green,TC (IEEE Transactions on Industrial Electronics, 2015)
High step-up ratio dc-dc converters with megawatt ratings are of interest in wind turbine interfaces and high-voltage direct-current systems. This paper presents a modular multilevel dc-dc converter based on the standard boost converter topology but with the normal single switches replaced by a number of capacitor-clamped submodules. The converter is operated in resonant mode with resonance between submodule capacitors and the arm inductor. A phase-shifted switching arrangement is applied such that there is a constant number, i.e., N, of submodules supporting the high voltage at a time. In this operation mode, the step-up ratio is dependent on the number of submodules and the inductor charging ratio. The converter exhibits scalability without using a transformer and is capable of bidirectional power flow. An application example of a wind turbine interface with a 10 : 1 conversion ratio is demonstrated in simulation. The experimental verification of the concept using a lab-scale prototype is provided.